Desafios do planejamento da expansão de geração do sistema elétrico brasileiro - Martins, Criciéle Castro (Universidade Federal do Pampa, 2015)
The Brazilian Power Industry (SEB) is characterized as hydrothermal, that is a dependence of both hydro and thermal generation. Climate variations that produce a low inflows system affected the production of hydroelectric power plants, resulting directly in increased use of reservoirs. Currently, the reservation capacity of Brazilian hydroelectric plants is limited, not more than six months, demanding that there are other sources of power generation to compose the SEB. The use of thermal plants to meet demand is related to the improvement of energy security of the electrical system, but its use raises the cost of the electricity generated. In 2001, there was a power rationing that lasted from June of that year until February 2002. Both climatic factors as the rapid growth in demand and the lack of investments contributed to the biggest crisis ever experienced in the energy system. The electricity rationing enacted by the National System Operator (ONS) meant there was a reduction in energy consumption, which prevented the complete emptying of the reservoirs at the time. After the rationing, the electricity supply has been addressed, especially by the media. Today Brazil is undergoing an intense period of drought which causes a severe depletion of reservoirs, despite now having a higher thermal capacity, better infrastructure of transmission between the electric and energetics subsystems and sophisticated computer programs, which aims to determine an optimal strategy of oper-ation of interconnected hydrothermal subsystems. The method adopted by the ONS is developed by the Center for Energy Research (CEPEL), known as NEWAVE contributes to operation better and electrical system efficiency. During the evolution of the electricity sector the operation planning method has also undergone reforms, adapting to such developments. This study evaluates the planning of the operation and expansion of the Brazilian electrical system from its evolution over the years. They are also analyzed and compared the energy crisis occurred in 2001 with the currently experienced situations, listing challenges and proposing possible improvements to the SEB.
Keywords: Electrical engineering; Electricity; Brazilian Electrical System; Engenharia elétrica; Energia elétrica; Sistema Elétrico Brasileiro; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA